Outcomes of Pediatric Supracondylar Fractures of Humerus Treated by Posterior Triceps Splitting Approach - Dwivedi, Rajeev; Joshi, Ruban Raj; Byanjankar, Subin; Shrestha, Rahul (Journal of Lumbini Medical College, 2017)
Introduction: Close reduction and percutaneous pinning is the gold standard treatment for supracondylar fracture of humerus. Open reduction and internal fixation is indicated in patients with unacceptable closed reduction, neurovascular compromise, and open fractures. Open reduction can be performed through various approaches. Every approach has their advantages and limitations. The aim of this study was to assess the functional and cosmetic outcome of pediatric supracondylar fracture of hummers treated by posterior triceps splitting approach. Methods: This was a prospective evaluation of 20 consecutive patients with displaced pediatric supracondylar humeral fractures operated by triceps spitting posterior approach in our institution for two years. At initial presentation, 19 cases were Gartland III and one was flexion variant of injury. Complications such as reduction loss, pin migration, infection, osteonecrosis of any part of the elbow, bone healing, and functional results were evaluated. Flynn criteria were used to evaluate the final results. Results: Twenty patients underwent open reduction and internal fixation by triceps splitting approach. Thirteen patients were male and seven were female with M:F ratio of 1.86:1. The mean age was 6.8 yr (SD=2.74, range 2-14). All the fractures united by six weeks; mean time for union was 4.5 wk (SD=0.94). All patients were assessed at six months using Flynn clinical and radiological criteria. Results were satisfactory in all patients. Conclusion: Posterior triceps splitting approach is simple, safe and has good functional and radiological outcome. We recommend this approach for open reduction and internal fixation in pediatric supracondylar fracture. DOI: https://doi.org/10.22502/jlmc.v4i1.83 J. Lumbini. Med. Coll. Vol 4, No 1, Jan-June 2016, Page: 28-31